Local fiscal equalization in Estonia : is a reform necessary? - Peter Friedrich; Chang Woon Nam; Janno Reiljan (Center for Economic Studies and ifo Institute (CESifo), 2009)
Estonian municipalities should perform a broad range of functions, while their fiscal resources are often limited and large disparities in fiscal capacity prevail among them. Moreover, the power to regulate fiscal affairs is mostly in the hands of the central government. We discuss how a strict application of the connexity principle can protect municipalities from the fiscal bottleneck. We also recommend the introduction of the principle of parallelism and investigate its effects on the unconditional, down-flow grant system in Estonia. In particular the procedure of determining the total sum of block grants appears to be changed.
Keywords: H27; H70; H77; R10; 330; fiscal equalization; municipal finance; connexity; principles of parallelism; Estonia; Gemeindefinanzen; Finanzpolitische Aufgabenverteilung; Kommunaler Finanzausgleich; Reform; Estland